Effect of CO2 sequestration on soil liquefaction in geological pits - T. Laxmi; H. M. Padhy; Pranati Mishra; Rohit Singh (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper deals with review of the previous related research onevaluation of soil liquefaction due toCarbon sequestration by various Carbon Capture Sequestration processesin geological pits. It providescritical literature recommendations on evaluation of soil liquefaction potential assessment. The detectionof soil liquefaction by using seismic records has been developed byvarious researchers. With thisinformation, the evaluation of soil liquefaction are well understood and this lead to a more preciseand confident output. Gaining support for CCS will require engagingthe interest and building thesupport of a variety of stakeholders, each with different perspectives and goals. Although, CCSbuilds upon a technology base developed over more than half a century by theoil and gas industry. In thepast, the industrially released CO2had been introduced to ocean which was harming the aquatic animals.In view of this, the sequestration of CO2into ocean was internationally banned